Exploration of serum biomarkers in heart failure patients with preserved and reduced ejection fractions through analysis of heterogeneity - Qipeng Jin; Zhicheng Wang; Wenyong Lin; Chunling Zhang; Xiaolong Wang (Biochemistry and Biophysics Reports, 2025)
Background: Heart failure with preserved ejection fraction (HFpEF) and heart failure with reduced ejection fraction (HFrEF) differ markedly in their pathophysiology. Distinguishing HFpEF remains challenging, particularly among patients with hypertension and metabolic syndrome. Methods: Untargeted metabolomics using liquid chromatography-tandem mass spectrometry (LC-MS/MS) was performed on serum samples from four groups: healthy controls (N), hypertensive patients with diabetes (H_A_T), HFpEF, and HFrEF. Key metabolites distinguishing HFpEF were identified using pathway enrichment analysis and random forest machine learning. ROC curve analysis evaluated their diagnostic accuracy. Results: A total of 3924 metabolites were identified. Amino acid and fatty acid metabolic pathways emerged as central to heart failure pathophysiology. Metabolites including DG(13:0/20:3(8Z,11Z,14Z)/0:0), glutarylcarnitine, homo-l-arginine, sphingosine, and (R)-3-hydroxybutyrylcarnitine were highlighted as diagnostic markers. A predictive model based on these metabolites effectively distinguished HFpEF from other subtypes, with enhanced specificity when combined with NT-proBNP. Conclusions: The identified serum metabolites show promise as early diagnostic biomarkers for HFpEF. Validation in larger, multicenter cohorts and further investigation into underlying biological mechanisms are necessary to confirm their clinical utility.